Nomogram for predicting testicular yolk sac tumor in children based on age, alpha-fetoprotein, and ultrasonography - Yu, Huan; Wang, Hui; Huang, Yichen; Hu, Huiyong; Zhang, Yue; Wu, Min; Lyu, Yiqing; Chen, Yan; Zhou, Lijun; Liang, Yan; Sun, Huizhen; Lin, Xiaoling; et al. (Frontiers in Pediatrics, 2024)
Objective: To establish a predictive model for distinguishing testicular benign or yolk sac tumors in children. Methods: We retrospectively analyzed data for 119 consecutive patients with unilateral testicular tumors treated at a single institution from June 2014 to July 2020. The patients were divided into the benign (n=90) and yolk sac (n=29) tumor groups based on the pathological diagnosis. We recorded patient age, serum markers (serum alpha-fetoprotein (AFP), human chorionic gonadotropin), and tumor ultrasonic findings (maximum diameter, ultrasonic echo, blood flow signal). Predictive factors were identified using descriptive statistical methods. A nomogram was established for preoperative prediction. An additional 46 patients were used as a validation cohort to verify the model. Results: Patients with testicular yolk sac tumors were younger (median age: 14.0 vs. 34.0 months, P=0.001) and had a higher incidence of elevated AFP levels (93.1% vs. 2.2%, P<0.001). Ultrasonography indicated that testicular yolk sac tumors tended to have larger maximum diameters (26.5±11.3 vs. 16.6±9.2 cm, P<0.001), a higher proportion of hypoechoic masses (44.8% vs. 8.9%, P<0.001), and a higher incidence of masses with strong blood flow signals (93.1% vs. 5.6%, P<0.001). A nomogram based on age, AFP levels, and ultrasound blood flow signals effectively predicted the probability of yolk sac tumor in children, with an accuracy of 0.98 (95% confidence interval: 0.984–1.003). The Brier score of the nomogram was 0.0002. Conclusion: A nomogram based on age, AFP levels, and ultrasound blood flow signals can effectively predict the probability of testicular yolk sac tumor preoperatively, aiding in clinical decision-making and patient counseling.